2017
DOI: 10.1080/01616412.2017.1312775
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial involvement in memory impairment induced by scopolamine in rats

Abstract: In conclusion, the present results indicate that SCO induced cognitive dysfunction and oxidative stress may involve brain mitochondrial impairment, an important target for new neuroprotective compounds against AD and other dementias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 66 publications
4
28
0
Order By: Relevance
“…Indeed, some data reported that mAChR activation increases neuronal vulnerability to oxidative stress 13 , while others that mAChR stimulation can generate ROS, involved in neuronal-signaling pathways 14,15 . Recently, two different research groups reported that scopolamine administration induced memory deficit and increased ROS levels 58,59 , in agreement with the present data showing a significant reduction of ROS levels at all-time points following acute Oxo treatment. In contrast, here we have not found significant ROS levels change in the rat group treated with scopolamine, probably due to different timing of ROS level detection, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, some data reported that mAChR activation increases neuronal vulnerability to oxidative stress 13 , while others that mAChR stimulation can generate ROS, involved in neuronal-signaling pathways 14,15 . Recently, two different research groups reported that scopolamine administration induced memory deficit and increased ROS levels 58,59 , in agreement with the present data showing a significant reduction of ROS levels at all-time points following acute Oxo treatment. In contrast, here we have not found significant ROS levels change in the rat group treated with scopolamine, probably due to different timing of ROS level detection, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Certain conditions, such as ongoing pathological processes (like those occurring in the AD brain) or other stressful stimuli, may either cause mitochondrial dysfunction and/or greatly limit mitochondrial access to glucose and production of pyruvate, leading to diminished synthesis of A-CoA and thereby ACh. Indeed, there are direct links between ACh and insulin secretion [43], and/or insulin resistance and Alzheimer’s disease [44], glucose metabolism [45], as well as mitochondrial dysfunction [46]. In such circumstances, a hypothetical pathway is that as a mean to maintain protective action of ACh through mt- nAChRs [39, 42], the reduced cytosolic A-CoA induces (7) translocation of ChAT into the cell nucleus, where ChAT somehow will participate in modulation of gene expression of various key proteins [47].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of scopolamine has been seen to induce several key features of AD, including cognitive impairments and the accumulation of A [155] . This model also exhibits increased oxidative stress [156,157] , and mitochondria with a higher vulnerability to swelling and membrane potential dissipation [158] . Another toxin induced model of AD is the administration of streptozotocin, which has been seen to induce cognitive impairments [159] , as well as the accumulation of both A and hyper-phosphorylated tau [160] .…”
Section: Toxin Induced Models Of Admentioning
confidence: 98%